Korelasi Asupan Zat Gizi Makro terhadap IMT pada Lansia Peserta Prolanis - Sutrio Sutrio; Arie Nugroho; Sefanadia Putri (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2026)
Optimal nutritional status is a primary indicator of successful chronic disease management within the Program Pengelolaan Penyakit Kronis (Prolanis). This study aimed to analyze the association between macronutrient intake (energy, protein, fat, carbohydrates, fiber, and cholesterol) and Body Mass Index (BMI) among Prolanis participants. A cross-sectional observational study was conducted on 42 elderly subjects, with a majority being female (69%) and aged 60–70 years (61.9%). Dietary intake was assessed using a 24-hour recall method and analyzed using Pearson/Spearman correlation and linear regression tests. The results revealed that 66.7% of subjects had never received nutritional counseling. Statistical analysis showed a significant positive correlation (p<0.05) between BMI and the intake of energy (r=0.517), protein (r=0.537), fat (r=0.747), carbohydrates (r=0.391), and fiber (r=0.671). No significant correlation was found between cholesterol intake and BMI (p=0.538). Regression analysis identified fat intake as the most dominant factor influencing BMI (B=0.949; p=0.002). In conclusion, macronutrient and fiber intake are closely associated with the nutritional status of the elderly, with fat identified as the primary determinant of BMI among Prolanis participants. Strengthening routine nutritional counseling programs is recommended to prevent nutritional issues in elderly patients with chronic diseases.